Critical evaluation of a possible role of HLA epitope matching in kidney transplantation - Kumru, Gizem; Unterrainer, Christian; Süsal, Caner (Transplantation reviews, 2020)
Human leukocyte antigen (HLA) matching is one of the cornerstones of organ allocation in deceased-donor kidney transplantation. Increased numbers of HLA allele mismatches are associated with a higher risk of immunological rejection, de novo donor-specific HLA antibody development and graft failure. HLA epitopes are defined as the specific portions of HLA molecules to which antibodies and T-cell receptors bind with their paratopes. The same epitope can be present on different HLA alleles. Therefore, HLA matching at the epitope instead of allele level theoretically offers a more precise assessment of donor-recipient HLA compatibility and may more effectively prevent sensitization against foreign tissue. In this review, we describe the different options proposed to define clinically relevant HLA epitopes and critically discuss the potential role of HLA epitope matching in kidney transplantation.
Gesehen am 02.04.2020